Necrotizing soft tissue infection of both ear lobules occurring concomitantly in a set of twins following non-aseptic ear piercing: a case report - U. U. Nnadozie; O. B. Ezeanosike; C. C. Maduba; D. C. Obu; U. S. D. Unigwe (BMC, 2020)
Abstract Background Necrotizing soft tissue infection of the ear following ear piercing is a very rare condition. It is easily misdiagnosed leading to reconstructive morbidities and mortality in neonates. High clinical suspicion is important for early diagnosis. Our knowledge, this is the first case reported in the literature in this unique initial presentation. We hope to heighten the awareness of necrotizing soft tissue infection of the ear following ear piercing to ensure early aggressive intervention. Case presentation We report a set of 19-day-old female twin neonates who developed bilateral ear sores following ear piercing in a primary healthcentre without adherence to surgical asepsis. Examination findings showed features consistent with necrotizing soft tissue infections of the ears. They were successfully managed with antibiotics and wound care. Conclusion Necrotizing soft tissue infections is a very rare complication of neonatal ear piercing. It may occur following suboptimal aseptic procedure and a high index of suspicion is necessary to make this diagnosis to ensure early intervention and to forestall the potential reconstructive morbidities and mortality associated with late recognition. Adherence to basic aseptic surgical principles is the key to prevention of necrotizing soft tissue infections.